Exploring challenges and opportunities of Remote Teaching at Nepalese Community Secondary Schools during Covid-19 Pandemic - Lal Lamsal, Hiranaya (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
In the Nepalese education system, synchronous teaching has not been practiced severely. Due to COVID-19 crisis, many schools are compelled to conduct the classes through virtual mode which is really a challenging phenomenon for the teachers especially in community schools. The main purpose of this study was to explore challenges and opportunities of remote teaching for teachers at Community Secondary Schools in Nepal. Whether they take this as a challenge of teaching or chance for learning. Employing a phenomological design of qualitative research, the researcher selected 26 teachers from 13 community secondary schools of Devdaha Municipality in Rupandehi district. From each of the schools, 2 secondary level teachers were chosen as the population purposively. The researcher designed a set of open-ended questions and conducted semi-structured interview to the teachers of each school in order to collect data for the research. In this study, the researcher focuses on the effectiveness and significance of remote teaching by exploring its obstacles, challenges, and opportunities for the teachers. The result of the study asserted that remote teaching is effective if the designated challenges and obstacles are addressed in an expected manner. The majority of the teachers responded that online teaching is such a platform that makes every teacher familiar with different kinds of resources and it always provides an opportunity for developing innovation and creativity. Similarly, virtual mode provides ample chances to boost communication towards various national and international conferences, online sessions, and so on. Online teaching creates opportunities to access and share information more easily and readily for the teachers at community schools in Nepal.